A 14-Day Course of Triple Therapy is Superior to a 10-Day Course for the Eradication of Helicobacter pylori: A Canadian Study Conducted in a ‘Real World’ Setting - Yen-I Chen; Carlo A Fallone (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Successful Helicobacter pylori eradication with the traditional seven-day course of proton pump inhibitor (PPI) triple therapy is declining. Prolonging therapy to either 10 or 14 days is associated with better eradications rates.